Online learning as a transformation in the academic system - Aliya, Zhakupova; Zhanat, Akbalayeva; Zhanar, Zhardamaliyeva; Sara, Koyanbekova; Zhanat, Ibragimova (International Journal of Innovative Research and Scientific Studies, 2025)
Online or distance education represents a departure from conventional learning methods, facilitating the idea that learners can be situated remotely from the primary sources of knowledge, whether they are through books, instructors, or peer groups. This approach empowers educational institutions to extend their offerings to a diverse range of geographical locations, granting learners the flexibility to engage with educational content and training programs from wherever they are. Such educational models cater particularly to students who may face barriers to participating in traditional classroom settings. This study seeks to explore both traditional and online teaching and learning methodologies, drawing upon existing research to inform its analysis. The findings suggest that while online education presents unique challenges, there remains optimism about its potential applicability, especially for specific demographics facing particular circumstances.